(untitled) (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2026)
This article examines the technological strategies of transnational corporations operating in the electrical engineering products market, as well as the role of research and development (R&D) in shaping their global competitive advantage. The primary objective of the study is to evaluate the determining factors of industrial leadership in the electrical engineering sector through a comparative analysis of the technological development models of “Intel,” “Samsung Electronics,” and “TSMC.” In the contemporary context, the advancement of artificial intelligence, 5G, the Internet of Things, and high-performance computing technologies has further intensified innovation-driven competition in the electrical engineering industry. According to the findings of the study, substantial R&D investments play a crucial role in achieving technological superiority; however, they are not sufficient on their own. Despite significant investment volumes, “Intel” has experienced a relative decline in its competitive position due to delays in manufacturing processes and limited organizational agility. “Samsung Electronics” has maintained a strong market position through a balanced innovation strategy and investments in HBM and DDR5 technologies. Meanwhile, “TSMC,” through its pure-play foundry model, early investments in advanced technologies, and a global customer network, has achieved higher efficiency and technological leadership. In the electrical engineering industry, sustainable competitive advantage depends not only on financial resources but also on strategic agility, effective innovation management, and integration into the global technological ecosystem.